Government-Linked Companies, Audit Quality, and Firm Size: Key Determinants of Firm Performance in Malaysia - Azman, Amirah Anis; Amir, Aliana Shazma; Zaidi, Zulaikha Rabitah; Isa, Evawaynie Valquis Md.; Hassan, Azlini Che (Universitas Medan Area, 2024)
This study investigates the roles of government-linked companies (GLCs), audit quality, and firm size as key determinants of firm performance among the top 100 companies in Malaysia from 2018 to 2022, measured by Return on Assets (ROA). The findings support agency theory, suggesting that GLCs, under government oversight, prioritize broader objectives over shareholder wealth maximization. Effective monitoring mechanisms, such as independent boards and audit committees, help reduce agency costs and enhance performance. Furthermore, higher audit quality is found to positively influence ROA, highlighting the significance of Big Four audit firms in protecting investor interests. Conversely, while firm size shows a negative correlation with ROA, this relationship is statistically insignificant, indicating that larger boards may not necessarily improve performance. In conclusion, this study contributes to the theoretical and practical understanding of how GLCs, audit quality, and firm size influence corporate growth. It identifies gaps in the existing literature regarding the implications of firm size and the effectiveness of governance structures. Future research should further explore these dimensions, particularly the optimization of governance mechanisms to enhance firm performance across different contexts.